SISTEM EKONOMI NEOLIBERALIS KAPITALISME DALAM PERSPEKTIF NILAI-NILAI ETIK ISLAM - Farihah, Umi (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
The existence of the system of Capitalism in economic activity is now clearly cause damage everywhere. Capitalism as a system of philosophy is already disabled since birth, because he was born of the paradigm of secularism. As an alternative, Islam provides a solution for the damage that has occurred by applying economic system based on the revelation, namely Islamic Economic System.